The Impact of Trust on the Relations between Ethical Leadership and Internal Whistleblowing Intention - Fitriningrum, Andriati; Pulungan, Andrey Hasiholan; Dewi, Ni Made Ayu Diah Pradnya; Imani, Nadya Nurul (Jurnal Dinamika Akuntansi dan Bisnis, 2022)
The aim of this study is to examine the impact of trust on the relationship between ethical leadership and internal whistleblowing intention. The study was motivated by the lack of willingness of organization members to blow the whistle on misconduct or unethical action internally compared to external whistleblowing. The willingness to blow the whistle internally is crucial, particularly to prevent negative impacts on the organization's performance and reputation. Using a quantitative method through a survey, this study examines 140 Indonesian public servants from one of the government directorates focused on perceptions of trust, ethical leadership, and internal whistleblowing intention. Using Structural Equation Modelling (SEM) and Partial Least Square (PLS), this study unveiled that the length of working periods determines the trust development. Meanwhile, feelings are key to an affective trust that influences ethical leadership to encourage the willingness of organization members to intentionally whistleblowing misconduct or unethical action internally.